Iridium-Catalyzed Formal [4+1] Annulation of Benzamides and Cyclopropanols to Afford Isoindolin-1-one Derivatives via C–H Activation - Xu, Shuran; Luo, Cankun; Yan, Kaichuan; Li, Jianglian; Lai, Ruizhi; Hai, Li; Guan, Mei; Wu, Yong (Synthesis, 2022)
An iridium-catalyzed reaction protocol has been developed to achieve the oxidative C–H/N–H annulation of benzamides with cyclopropanols as C1 synthon. Structurally diverse isoindolin-1-ones were furnished via sequential C–H/C–C cleavage and C–C/C–N bond formation.
Keywords: C–H activation; benzamides; cyclopropanols; C–N bond formation; isoindolin-1-ones